Draft Annual Plan 2010-11 Volume-I (General Profile and Sectoral Programmes) Government of Uttarakhand - Planning Commission (Planning Commission, 2010)
Uttarakhand, having completed about 9 years as a separate state, is now poised to embark on a new era of rapid and inclusive growth and all-round development. The initial teething problems of a new state have been faced and solved to some extent, The broad features of the administrative structure and systems, extending from the state to the district and sub-district levels, are now in place, though the problem of shortage of manpower in crucial areas remains.
State Planning Commission, Government of Uttarakhand